Discovery of pyrrole derivatives as acetylcholinesterase-sparing butyrylcholinesterase inhibitor - Sun, Shouyuan; Shi, Tao; Peng, Yan; Zhang, Honghua; Zhuo, Linsheng; Peng, Xue; Li, Qien; Wang, Manxia; Wang, Shuzhi; Wang, Zhen (Frontiers in Pharmacology, 2022)
Inspired by the crucial roles of (hetero)aryl rings in cholinesterase inhibitors and the pyrrole ring in new drug discovery, we synthesized 19 pyrrole derivatives and investigated their cholinesterase inhibitory activity. As a result, compounds 3o, 3p, and 3s with a 1,3-diaryl-pyrrole skeleton showed high selectivity toward BChE over AChE with a best IC50 value of 1.71 ± 0.087 µM, which were comparable to donepezil. The pharmaceutical potential of these structures was further predicted and compounds 3o and 3p were proved to meet well with the Lipinsky's five rules. In combination of the inhibition kinetic studies with the results of molecular docking, we concluded that compound 3p inhibited BChE in a mixed competitive mode. This research has proved the potential of the 1,3-diaryl-pyrrole skeleton as a kind of selective BChE inhibitor.